Patients' perceptions on clinics service quality - Shaleh, Mohammad Khairul (Penerbit UTM Press, 2009)
In Malaysia, the demand for better quality in health service continues to rise in view of the growing population, changes in structure of population due to the increase in the number of the elderly, increase of consumer awareness with the shift of population distribution from rural to urban areas and the rationalization of the industry in this country. These changes forced greater emphasis to improve the healthcare services provided in the country. There are currently 150 government hospitals and 3000 clinics in Malaysia. All the thirteen states in Malaysia have their own government hospitals and government clinics that serve every town and village in the country. The Ministry of Health (MOH) has also approved the licenses of 214 private hospitals and 70 private or NGO-sponsored hemodialysis centers. (UNCTAD 1992). Even though the healthcare industry in Malaysia is not as competitive as compared to other more advanced countries like the United States and Japan, it doesn’t mean that the quality of the healthcare services need not be evaluated. Since Malaysia has started to focus on the healthcare industry as an alternative support industry as their income other than manufacturing industry, therefore there is a need for an evaluation or assessment on the quality of the healthcare services provided in order to make it more competitive. There are numerous researches conducted in the service quality of retail services worldwide. Most of the studies are focusing on customer perceptions and the providers’ expectations on the service quality. However, the number of studies conducted in healthcare services especially in the clinic’s service is less significant. Earlier studies in Thailand showed that healthcare personnel mostly underestimate the patient’s perceptions on their service (Kochapakdee, 1998; and Summartwart, 1997). The finding based on all the five dimension in accordance to SERVQUAL instruments as proposed by Parasuraman et al.(1988), showed that assurance (knowledge and courtesy of service provider and ability to inspire trust and confidence to patients) was the major contributor to the service quality for healthcare service. The main objective of the research is to determine the perceptions on the service quality of the clinics that served for HCJ (Not real name) based on the patients’ view. The study was also intended to focus on the secondary objectives that are to determine: (a) the differences between all the five dimensions of SERVQUAL to the service quality of the clinics; (b) the rank of all the five dimensions based on their importance based on the customers’ (patients) view; and (c) the validity and reliability of the modified SERVQUAL instruments in determining patient perceptions of the clinics service quality for HCJ employees.